Multi-Sector Bond Funds in Emerging Markets-Easy Come, Easy Go - Cortes, Fabio (International Monetary Fund, 2021)
Unconstrained multi-sector bond funds (MSBFs) can be a source of spillovers to emerging markets and potentially exert a sizable impact on cross-border flows. MSBFs have grown their investment in emerging markets in recent years and are highly concentrated-both in their positions and their decision-making. They typically also exhibit opportunistic behavior much more so than other investment funds. Theoretically, their size, multisector mandate, and unconstrained nature allows MSBFs to be a source of financial stability in periods of wide-spread market turmoil while others sell at fire-sale prices. However, this note, building on the analysis of Cortes and Sanfilippo (2020) and incorporating data around the COVID-19 crisis, finds that MSBFs could have contributed to increase market stress in selected emerging markets. When faced with large investor redemptions during the crisis, our sample of MSBFs chose to rebalance their portfolios in a concentrated manner, raising a large proportion of cash in a few specific local currency bond markets. This may have contributed to exacerbating the relative underperformance of these local currency bond markets to broader emerging market indices.